(untitled) (Research, Society and Development, 2023)
The increase in the number of elderly people in the population is remarkable. During aging, new difficulties arise, such as the decline of auditory and cognitive abilities. Much has been shown about the relationship between hearing loss and cognitive decline. Among the main consequences of this association are the difficulty in understanding speech, especially in noisy environments, and, therefore, increased listening effort. One intervention that has been shown to be effective is the use of a sound amplification device (SAD). The objective was to investigate auditory and cognitive aspects in elderly people with hearing loss. Fifty-six elderly people were evaluated at the beginning of the SAD adaptation process. The survey was carried out on the day of fitting and three procedures were performed: assessment of speech recognition in noise (SRN), with and without SAD, to calculate the Benefit, cognitive screening (CS) and subjective assessment of listening effort. It was observed that 32.1% of the individuals studied had results suggestive of cognitive impairment. Through regression models, it was observed that the Benefit average increases when the Best Ear Average value increases, the SRN Sound Level (SL) average without SAD decreases when the CS total score increases, and the SRN SL average without SAD increases as age increases. It was concluded that, with aging, worse is the performance on the CS, which may mean a worse performance on the SRN test. However, the use of SAD enables a better performance in the SRN test.